2022
DOI: 10.1029/2021ms002653
|View full text |Cite
|
Sign up to set email alerts
|

Representing Irrigation Processes in the Land Surface‐Hydrological Model and a Case Study in the Yangtze River Basin, China

Abstract: Irrigation is the dominant section of human water use, exerting essential impacts on hydrological processes and water resources. To more realistically simulate irrigation processes in water‐rich regions, an irrigation scheme is incorporated into a land surface‐hydrological model. It calculates the irrigation water requirement according to meteorological conditions, cropping area and growing stage, and root‐zone soil moisture, and determines the irrigation water withdrawal based on the available water resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…One motivation in developing coupled atmospheric and hydrological models is to improve parameterization schemes for water cycling processes, and then enhance simulating and forecasting accuracy. Some hu-man activities, e.g., reservoir impounding and regulation, groundwater extraction and irrigation, can significantly alter hydrological processes and the water cycle [98][99][100][101][102][103].…”
Section: Difficulties and Challengesmentioning
confidence: 99%
“…One motivation in developing coupled atmospheric and hydrological models is to improve parameterization schemes for water cycling processes, and then enhance simulating and forecasting accuracy. Some hu-man activities, e.g., reservoir impounding and regulation, groundwater extraction and irrigation, can significantly alter hydrological processes and the water cycle [98][99][100][101][102][103].…”
Section: Difficulties and Challengesmentioning
confidence: 99%
“…Studies have shown that the cooling effects of irrigation may be underestimated by global climate models due to their coarse spatial resolutions (Chen & Dirmeyer, 2020; Sorooshian et al, 2011). Irrigation datasets are required to both model and evaluate irrigation schemes and parameterizations, with information required for four key properties of irrigation: where, when, how, and how much to irrigate (Xia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our model development builds on the offline mode of the coupled Atmospheric and Hydrological Modelling System (AHMS), developed at the University of Cologne (Jiang et al, 2020;Xia, 2019). An example of the AHMS applications to wet hydrological basins can be found in Xia et al (2022). The use of river water and groundwater for irrigation in the Yellow River Basin is expected to profoundly impact the regional hydrological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Atmospheric and Hydrological Modelling System (AHMS) is a fully coupled atmospheric and hydrological modelling system (Jiang et al, 2020;Xia, 2019;Xia et al, 2022). Specifically, AHMS couples the Weather Research and Forecasting (WRF) modelling system (Skamarock & Klemp, 2008) with the physically-based distributed regional Hydrological Model System HMS (Yu et al, 2006) through the Noah-Multiparameterziation Land Surface Model (Noah-MP; Chen & Dudhia, 2001;Niu et al, 2011).…”
Section: Introduction Of the Offline Atmospheric And Hydrological Mod...mentioning
confidence: 99%
See 1 more Smart Citation